Peningkatan Kemandirian Warga Kampung Susun Kunir melalui Panduan Perizinan UMKM - Rona Fika Jamila; Gentina Pratama Putra (CV. IRA PUBLISHING, 2026)
For MSMEs, legality is crucial, as it provides legal certainty and empowers them to develop their businesses. Legality for MSMEs is typically known as a Micro, Small, and Medium Enterprise Permit (IUMK). While business space in Kampung Kunir has been provided, its utilization is still suboptimal. Instead, residential areas are being used for business. However, not all MSMEs have business permits, or they are unaware of the process. The purpose of this Community Service Program is to educate MSMEs on how to obtain permits for their products, equip them with awareness and a willingness to be